ANALISIS KUALITAS SUMBER DAYA APARATUR PADA KANTOR KELURAHAN BERENG KECAMATAN KAHAYAN HILIR KABUPATEN PULANG PISAU: Analysis Of The Quality Of Apparatus Resources At The Office Of Kelurahan Bereng Kecamatan Kahayan Hilir Kabupaten Pulang Pisau - Rochman, Wisnu Nur; Nurhasanah, Nurhasanah; Mambang, Mambang (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The purpose of this study was to analyze the Quality of Apparatus Resources at the Bereng Village Office, Kahayan Hilir District, Pulang Pisau Regency. In this study, the author uses descriptive qualitative research with data collection techniques, namely observation, interviews, and documentation. Data analysis with descriptive analysis model to describe the actual situation about the object under study according to the actual situation. The results of the study stated that the quality of apparatus resources at the Bereng Village Office, Kahayan Hilir District, Pulang Pisau Regency when adjusted to the framework of thinking that refers to Ability, Knowledge, Skills is as follows. From the aspect of ability, namely the ability that is formed from a number of competencies possessed by an employee which includes loyalty, discipline, cooperation and responsibility, the apparatus at the Bereng Village Office can be categorized quite well in terms of loyalty, discipline, cooperation and responsibility. For the Knowledge Aspect, namely the abilities possessed by employees who are more oriented towards intelligence and thinking power as well as broad knowledge mastery possessed by employees, but for the knowledge aspect, the existing apparatus resources are still lacking because the educational background of each employee is dominated by high school coupled with the development of increasingly advanced technology and the use of massive applications that not all employees are able to master.